Gastos com Antipsicóticos Atípicos, serviços ambulatoriais e hospitalares no tratamento da Esquizofrenia: Uma coorte de onze anos no Brasil - Wallace Breno Barbosa (2015)
Introduction: Schizophrenia is a serious, chronic and debilitating mental disorder. Treatment of schizophrenia consists primarily of using antipsychotics and psychosocial therapies. In Brazil, they have been stimulated therapeutic practices aimed at the inclusion of the patient in the community and its institutionalization. The strategy is progressively take over care at the psychiatric hospital for other alternatives and services in hospitals, such as psychiatric units in general hospitals, and outpatient care, as the Centers for Psychosocial Care (CAPS) and the Therapeutic Residences Services (RT). The Brazilian Public Health System (SUS) provides, in addition to hospital and outpatient treatment, typical antipsychotics, or first-generation (FGA), and atypical antipsychotics, or second generation (SGA). The ASG are treated as specialized medicines and dispensed to patients after analysis of compliance with requirements contained in the specific national clinical protocol. Objective: To describe the costs with the use of atypical antipsychotics and outpatient and hospital services for patients diagnosed with schizophrenia and attended by SUS, in Brazil, from a cohort from January 2000 to December 2010. Methods: National Cohort based on data from the SUS Outpatient Information System and Hospital Information System. Spending was stratified by procedures and categories of procedures. Subsequently, we calculate the median spending by categories of procedures, grouped according to the atypical antipsychotic used by the patient in the cohort entry, considering the intention to treat, and present these spending in the period and year of follow-up. Results: We included 241,079 patients, 50.3% male, mean age 45 years; 66.1% lived in the southeast and 1.7% in northern Brazil; 19.1% of patients started treatment in 2010 and 2.8% in 2000; 82.8% of patients remained with the input medicament in the cohort; 40.7% of patients used olanzapine, risperidone (40.5%), quetiapine (20.8%), and ziprasidone (11.5%) and clozapine (7.2%).The total cohort spent was BRL 1,987,509,756.62; whereas 82.9% of spending was with drugs, 9.8% with hospitalizations and to 7.3% with outpatient procedures. Atypical antipsychotics accounted for 77.7% of spending (median of BRL 874.29), psychiatric hospitalizations (6.6% to BRL 1,815.20) and outpatient psychiatric care (5.6% to BRL 513.01). The largest proportion of spending on drugs was observed with olanzapine (56.3%). The psychiatric care accounted for 74.9% of outpatient expenditures and treatment in psychiatry 66.9% of hospital expenses. The median spending antipsychotics and psychiatric hospitalization increased during the study period, on the other hand spending on outpatient psychiatric monitoring reduced. The median cost of olanzapine as an entry product in the cohort was BRL 1,820.45, ziprasidone (BRL 1,601.35), clozapine (BRL 1,355.06), quetiapine (BRL 1,040.09) and risperidone (BRL 49.42). Patients who used clozapine at the entrance had higher median spending on psychiatric hospitalizations (BRL 2,553.43) and outpatient psychiatric care (BRL 626.60). Conclusion: Antipsychotic were responsible for most of the expenses in the period. Olanzapine was the most used, with the highest total expenditure and the biggest median spending among antipsychotics. Psychiatric hospitalizations account for higher median spending and lower percentage of patients using these services, already outpatient psychiatric care had the lowest median spending. The results of this study are relevant and print the SUS the need to optimize their spending, encouraging the rational use of antipsychotics and increased use of outpatient psychiatric services.